Emergency Evaluation and Management of Encephalitis and Myelitis in Adults - Bradshaw, Michael J.; Venkatesan, Arun (Seminars in Neurology, 2019)
Infection of the central nervous system is often a life-threatening emergency. In many cases, the clinician faces an unknown pathogen and must rely upon clinical acumen and a thorough, systematic diagnostic investigation to establish a diagnosis and initiate appropriate treatment. Because patients typically present with a syndrome, such as temporal lobe encephalitis, rather than a known pathogen (e.g., herpes simplex virus 1 encephalitis), we describe diagnostic considerations in the context of their neuroanatomic tropisms and patterns of disease. This paradigm reflects the challenges clinicians face; however, tropisms are not absolute, patterns of disease are not specific, and this approach does not obviate the need for empirical treatment while a systematic diagnostic investigation is underway. Specific treatment is available for many infectious agents, including bacterial, fungal, and parasitic pathogens, as well as the herpesviruses. In cases with no specific treatment, clinicians must strive to establish the diagnosis (and thereby spare unneeded treatment), anticipate and recognize complications and pitfalls, and initiate appropriate supportive care, all of which are best achieved with a well-prepared multidisciplinary team.
Keywords: meningitis; encephalitis; myelitis; infectious; emergency